Answer:
The value of the expression 8 - I2g - 5I is -4 ⇒ D
Explanation:
The absolute value always gives a positive value IaI = a and I-aI = a
Let us solve the question
∵ The expression is 8 - I2g - 5I
∵ The value of g is g = -3.5
→ To find the value of the expression substitute g by -3.5
∵ 8 - I2g - 5I = 8 - I2(-3.5) - 5I
∴ 8 - I2g - 5I = 8 - I-7 - 5I
∴ 8 - I2g - 5I = 8 - I-12I
→ By using the rule above
∵ I-12I = 12
∴ 8 - I2g - 5I = 8 - 12
∴ 8 - I2g - 5I = -4
∴ The value of the expression 8 - I2g - 5I is -4